Efficacy of Herbal Lysine Supplementation on Broiler Performance - Kathirvelan, C.; Purushothaman, M.R.; Janani, S.R.; Banupriya, S. (Indian Journal of Animal Nutrition, 2018)
A trial was conducted for a period of 42 days to assess the comparative efficacy of the herbal and synthetic lysine on the performance of broilers. A total of 160 day old Vencobb broiler male chicks were divided into five groups each group having four replicates of eight birds. The birds in group T1 were fed standard ration without herbal and synthetic source (Control), T2 (25% herbal lysine: 75% synthetic lysine, T3 (50% herballysine: 50% synthetic lysine), T4 (75% herbal lysine: 25% synthetic lysine) and T5 (100% herbal lysine). The higher weight gain (2135Â±48) and better feed efficiency (1.734Â±0.059) was found in T3 when compared to control and other treatment groups. Dressing percentage, heart, liver, kidney, gizzard weight, abdominal fat and intestinal length did not vary among the groups. Albumin, albumin: globulin ratio, triglycerides, totalcholesterol, HDL, LDL, AST and ALT status of the birds were comparable with the control. The liver and breast muscle lipid content was lower in treatment T 2 as compared to control (T1) whereas in thigh, it was high. Supplementation of herbal and synthetic lysine at 50: 50 was found to provide better returns (` 2.12 per kg) over that of control. Therefore, it could be concluded that supplementation of herbal and synthetic lysine (50: 50) in broiler diet improved the performance of birds and reduced the feed cost per unit weight gain.